A crush resistant, abrasion resistant cable and method of making the same

CN122898077APending Publication Date: 2026-10-13GUANGDONG FENGLIN OPTICAL COMMUNICATIONS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611313684.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这种迁移将会使聚氯乙烯相因增塑剂减少而重新变硬,导致其力学性能、弹性和增韧效果显著下降

Benefits of technology

本发明制备了一种同时带有磷酸酯结构、长链烷基结构、喹啉环结构、双键结构的反应型阻燃增塑剂,并将该反应型阻燃增塑剂接枝在热塑性聚氨酯弹性体中对其改性。反应型阻燃增塑剂中的喹啉环结构使其在聚氯乙烯相中具有更好的相容性,本发明将其接枝在热塑性聚氨酯弹性体中,不仅能够阻止反应型阻燃增塑剂本身的迁移,其中的喹啉环结构还能够与聚氯乙烯基体中的氯原子形成可逆的卤键从而增强改性热塑性聚氨酯弹性体相与聚氯乙烯相之间的界面结合力,促进改性热塑性聚氨酯弹性体在聚氯乙烯相中的分散,并使改性热塑性聚氨酯弹性体相与聚氯乙烯相之间的结合更加紧密,进而有效抑制材料中其他未接枝的小分子增塑剂向两相界面或材料表面迁移。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898077A_ABST
    Figure CN122898077A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of extrusion-resistant wear-resistant cable and its preparation method, belong to cable technical field;The present application prepares a kind of reactive flame-retardant plasticizer with phosphate structure, long-chain alkyl structure, quinoline ring structure, double bond structure simultaneously, and the reactive flame-retardant plasticizer is grafted in thermoplastic polyurethane elastomer and is modified, effectively solve the migration problem of plasticizer;And using the better characteristics of the compatibility of reactive flame-retardant plasticizer in polyvinyl chloride phase, it is grafted on the thermoplastic polyurethane elastomer with poor compatibility and modified, using the enrichment tendency of reactive flame-retardant plasticizer to enhance the interfacial bonding force between modified thermoplastic polyurethane elastomer phase and polyvinyl chloride phase, promote the dispersion of modified thermoplastic polyurethane elastomer in polyvinyl chloride phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable technology, specifically relating to an extrusion-resistant and abrasion-resistant cable and its preparation method. Background Technology

[0002] Polyvinyl chloride (PVC) is a commonly used material for the outer sheath of wires and cables, possessing good chemical resistance, insulation, and processability. However, pure PVC is hard and brittle, and usually requires the addition of a large amount of small-molecule plasticizers to impart flexibility and processability. Small-molecule plasticizers mainly soften the material by inserting into the polymer molecular chain, increasing the free volume of the system, and acting as a lubricant similar to a "ball bearing" between the polymer molecular chains, thus reducing friction between the molecular chains.

[0003] However, due to the lack of chemical bonding between small-molecule plasticizers and polyvinyl chloride (PVC) elastomers, migration, volatilization, or extraction are inevitable during long-term use, exposure to heat, contact with media, or mechanical stress. Plasticizer migration directly leads to the rapid loss of plasticizing effect, causing the material to harden and become brittle again, and may cause problems such as surface stickiness, dust attraction, and contamination. This migration problem is particularly prominent in composite materials with differences in polarity between the two phases. For example, in PVC / thermoplastic polyurethane elastomer composites, the compatibility between commonly used small-molecule polyester plasticizers in PVC and the soft segments of thermoplastic polyurethane elastomers is often better than their compatibility with PVC. Due to the difference in affinity between the two phases for the plasticizer, the plasticizer tends to migrate from the PVC phase to the thermoplastic polyurethane elastomer phase. This migration causes the PVC phase to harden again due to the reduction of plasticizer, resulting in a significant decrease in its mechanical properties, elasticity, and toughening effect. Meanwhile, the enrichment and migration of plasticizers at the phase interface can weaken the interfacial bonding between the two phases, resulting in poor stress transmission and ultimately reducing the overall performance of the material to varying degrees. Summary of the Invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide an extrusion-resistant and abrasion-resistant cable and a method for preparing the same.

[0005] This invention provides an extrusion-resistant and abrasion-resistant cable, comprising, from the inside out, a conductor core, an insulating silicone rubber layer, a polypropylene filler rope, a tinned copper wire shielding layer, a galvanized steel wire armor layer, and an outer sheath.

[0006] Preferably, the outer protective layer comprises the following raw materials in parts by weight: 100 parts by weight of polyvinyl chloride, 20-40 parts by weight of thermoplastic polyurethane elastomer, 5-10 parts by weight of reactive flame retardant plasticizer, 5-8 parts by weight of secondary flame retardant, 0.1-0.5 parts by weight of initiator, 3-5 parts by weight of heat stabilizer, 15-30 parts by weight of plasticizer, 8-15 parts by weight of reinforcing filler, 1-2.5 parts by weight of silane coupling agent, 0.5-2 parts by weight of lubricant, 0.8-1.5 parts by weight of antioxidant, and 0.8-1.5 parts by weight of light stabilizer.

[0007] Preferably, the secondary flame retardant is at least one of antimony trioxide and zinc borate.

[0008] Preferably, the initiator is at least one of dicumyl peroxide and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0009] Preferably, the heat stabilizer is at least one of calcium-zinc stabilizer CZ108 and calcium-zinc stabilizer CZ113.

[0010] Preferably, the plasticizer is at least one selected from epoxidized soybean oil, trioctyl trimellitate, and diisononyl cyclohexane-1,2-dicarboxylate.

[0011] Preferably, the reinforcing filler is at least one of nano-calcium carbonate, nano-silica, and calcined kaolin.

[0012] Preferably, the lubricant is at least one of polyethylene wax and oxidized polyethylene wax.

[0013] Preferably, the silane coupling agent is at least one selected from 3-chloropropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-bromopropyltriethoxysilane, and 3-bromopropyltrimethoxysilane.

[0014] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 1035, antioxidant 168, and antioxidant 626.

[0015] Preferably, the light stabilizer is at least one of UV-326, UV-327, UV-328, HALS-770, and HALS-622.

[0016] Preferably, the reactive flame retardant plasticizer is prepared by the following steps: S101. Under a nitrogen atmosphere, 18 parts by mass of 2-amino-5-nitrobenzoic acid, 7.2-10.8 parts by mass of acetone, 0.7-1.4 parts by mass of N,N-dimethylformamide, and 100-150 parts by mass of polyphosphoric acid are mixed and reacted at 120-140℃ for 4-6 hours. After the reaction is completed, the reaction solution is poured into a saturated sodium bicarbonate solution, the precipitate is separated by filtration, and the precipitate is washed with deionized water until neutral and then purified by silica gel column chromatography to obtain 2-methyl-6-nitroquinoline-4-ol. S102. Under a nitrogen atmosphere, 26-37 parts by mass of long-chain fatty alcohol, 15 parts by mass of phosphorus oxychloride, 24-30 parts by mass of triethylamine, and 260-320 parts by mass of dichloroethane are mixed and reacted at a temperature of 20-60℃ for 6-24 hours. After the reaction is completed, triethylamine hydrochloride is removed by filtration, and then the solvent and excess triethylamine in the filtrate are removed by rotary evaporation to obtain the flame retardant precursor. S103. Under a nitrogen atmosphere, 12 parts by mass of 2-methyl-6-nitroquinoline-4-ol, 27-35 parts by mass of flame retardant precursor, 9.8-12.2 parts by mass of triethylamine, and 200-240 parts by mass of dichloroethane are mixed and reacted at a temperature of 40-60℃ for 12-24 hours. After the reaction is completed, the solvent in the reaction solution is removed by rotary evaporation. The remaining solid is then washed with deionized water and dried to obtain the flame retardant plasticizer precursor. S104. Under a nitrogen atmosphere, 24-30 parts by weight of flame retardant plasticizer precursor, 9.4-15.6 parts by weight of zinc powder, 11.6-15.4 parts by weight of ammonium chloride, 96-120 parts by weight of anhydrous ethanol, and 36-48 parts by weight of deionized water are mixed and reacted at 80-90℃ for 2-4 hours. After the reaction is completed, the reaction solution is poured into a saturated sodium bicarbonate solution and then extracted with ethyl acetate. After separating the organic phase, the solvent is removed by rotary evaporation of the organic phase to obtain the flame retardant plasticizer. S105. Mix 3.8-5.2 parts by weight of acryloyl chloride, 18-22 parts by weight of flame retardant plasticizer, 4.7-5.9 parts by weight of triethylamine, and 100-120 parts by weight of dichloroethane and react at 0-20°C for 1-3 hours. After the reaction is complete, remove the solvent from the reaction solution by rotary evaporation, and wash the remaining solid with deionized water and dry it to obtain the reactive flame retardant plasticizer.

[0017] Preferably, the long-chain fatty alcohol is at least one of n-octanol, n-decanol, and lauryl alcohol.

[0018] Furthermore, the present invention also provides a method for preparing the extrusion-resistant and abrasion-resistant cable as described above, comprising: S201. Mix 8-15 parts by weight of reinforcing filler, 1-2.5 parts by weight of silane coupling agent, and 80-150 parts by weight of 40-60% ethanol aqueous solution and react at 40-60℃ for 3-6 hours. After the reaction is completed, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler.

[0019] S202. The thermoplastic polyurethane elastomer, reactive flame retardant plasticizer, and initiator are mixed and added to a screw extruder. The mixture is then melt-extruded and granulated at a temperature of 170-180℃ to obtain the modified thermoplastic polyurethane elastomer. S203. The conductor cores of the conductor stranded together are arranged in parallel, an insulating silicone rubber layer is wrapped around the conductor, and a polypropylene filler rope is used to fill the gap. A tinned copper wire shielding layer is woven to wrap the conductor cores and the polypropylene filler rope together. Then, a galvanized steel wire armoring layer is woven outside the tinned copper wire shielding layer. S204. Polyvinyl chloride, modified thermoplastic polyurethane elastomer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant, and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 165-175℃, the mixture is coated onto the outside of a galvanized steel wire armor layer to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 80-100℃ for 4-8 hours to form an outer sheath layer on the outside of the galvanized steel wire armor layer, thus obtaining an extrusion-resistant and wear-resistant cable.

[0020] Compared with the prior art, the present invention has the following beneficial effects: This invention prepares a reactive flame-retardant plasticizer possessing a phosphate ester structure, a long-chain alkyl structure, a quinoline ring structure, and a double bond structure. This reactive flame-retardant plasticizer is then grafted onto a thermoplastic polyurethane elastomer for modification. The quinoline ring structure in the reactive flame-retardant plasticizer enhances its compatibility with the polyvinyl chloride (PVC) phase. Grafting this plasticizer onto the PVC not only prevents the migration of the reactive flame-retardant plasticizer itself, but the quinoline ring structure can also form reversible halogen bonds with chlorine atoms in the PVC, thereby strengthening the interfacial bonding between the modified PVC elastomer phase and the PVC phase. This promotes the dispersion of the modified PVC elastomer in the PVC phase and makes the bond between the two phases tighter, effectively inhibiting the migration of other ungrafted small-molecule plasticizers to the interface or surface of the material.

[0021] The reactive flame retardant plasticizer prepared in this invention, after grafting, has a quinoline ring structure that can form reversible halogen bonds with chlorine atoms in the polyvinyl chloride phase. The long-chain alkyl groups in the reactive plasticizer can increase the free volume of the chain segments near the reactive plasticizer and reduce the kinetic energy barrier of the nearby chain segments, thereby significantly improving the efficiency of halogen bond breaking and recombination. This can better exert the plasticizing effect of the reactive flame retardant plasticizer at the gel theory level (i.e., breaking the original physical cross-linking points between molecular chains) and inhibit irreversible slippage of molecular chains, significantly improving the elastic recovery ability and creep resistance of cables.

[0022] The reactive flame-retardant plasticizer prepared by this invention has both a phosphate ester structure and a quinoline ring structure. It can not only exert a synergistic effect of nitrogen and phosphorus flame retardancy, but also anchor the secondary flame retardant through the coordination effect of the phosphate ester structure and the quinoline ring structure on the metal ions in antimony trioxide or zinc borate, promote the flame retardant synergy between different elements, and make the material have better flame retardant performance. Thus, it can meet the flame retardant requirements with a lower amount of flame retardant added, and better take into account the mechanical properties of the cable.

[0023] This invention uses a silane coupling agent with halogen atoms to modify the reinforcing filler, which greatly enhances the compatibility of the reinforcing filler in polyvinyl chloride matrix, and enables the reinforcing filler to generate halogen bond interactions and dipole interactions with the quinoline ring and phosphate ester structure in the reactive flame retardant plasticizer. This significantly improves the interfacial bonding force between the modified reinforcing filler and the polymer matrix, and improves the wear resistance of the cable. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the cross-sectional structure of the extrusion-resistant and wear-resistant cable of the present invention. In the figure, 1 is the conductor core; 2 is the insulating silicone rubber layer; 3 is the polypropylene filler rope; 4 is the tinned copper wire shielding layer; 5 is the galvanized steel wire armor layer; and 6 is the outer sheath.

[0025] Figure 2 This is a schematic diagram of the preparation process of the reactive flame retardant plasticizer of the present invention.

[0026] Figure 3 This is a schematic diagram of the infrared spectrum of the reactive flame retardant plasticizer obtained in Example 1. Detailed Implementation

[0027] It should be understood that the expression “one or more of…” individually includes each of the objects described after the expression, as well as various different combinations of two or more of the described objects, unless otherwise understood from the context and usage. The expression “and / or” combined with three or more described objects should be understood to have the same meaning, unless otherwise understood from the context.

[0028] The terms “including,” “having,” or “containing,” including the use of their grammatical synonyms, should generally be understood as open-ended and non-restrictive, for example, not excluding other unstated elements or steps, unless otherwise specifically stated or understood from the context.

[0029] It should be understood that the order of steps or the sequence of actions is not important as long as this application remains operational. Furthermore, two or more steps or actions may be performed simultaneously.

[0030] The use of any and all instances or exemplary language such as “e.g.” or “including” herein is merely intended to better illustrate the application and does not constitute a limitation on the scope of the application unless the claims are made. No language in this specification should be construed as indicating that any unclaimed element is essential to the practice of this application.

[0031] Furthermore, the numerical ranges and parameters used to define this application are approximate values, and the relevant values ​​in the specific embodiments have been presented as precisely as possible. However, any numerical value inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise explicitly stated, it should be understood that all ranges, quantities, values, and percentages used in this disclosure are modified with the word "approximately." Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a specific value or range.

[0032] The present invention is further illustrated below with reference to the embodiments. The scope of protection of the present invention is not limited to the following embodiments. Example

[0033] like Figure 1 The extrusion-resistant and wear-resistant cable includes, from the inside out, a conductor core 1, an insulating silicone rubber layer 2, a polypropylene filler rope 3, a tinned copper wire shielding layer 4, a galvanized steel wire armor layer 5, and an outer sheath 6.

[0034] In this embodiment, the outer protective layer comprises the following parts by weight of raw materials: 100 parts by weight of polyvinyl chloride, 20 parts by weight of thermoplastic polyurethane elastomer, 5 parts by weight of reactive flame retardant plasticizer, 5 parts by weight of secondary flame retardant, 0.1 parts by weight of initiator, 3 parts by weight of heat stabilizer, 15 parts by weight of plasticizer, 8 parts by weight of reinforcing filler, 1 part by weight of silane coupling agent, 0.5 parts by weight of lubricant, 0.8 parts by weight of antioxidant, and 0.8 parts by weight of light stabilizer.

[0035] In this embodiment, the thermoplastic polyurethane elastomer used is a polyester-type thermoplastic polyurethane elastomer with a Shore A hardness of 82. The secondary flame retardant used is antimony trioxide, the initiator used is dicumyl peroxide, the heat stabilizer used is calcium-zinc stabilizer CZ108, the plasticizer used is a mixture of 5 parts by weight of epoxidized soybean oil and 10 parts by weight of trioctyl trimellitate, the reinforcing filler used is nano-calcium carbonate, the lubricant used is polyethylene wax, the silane coupling agent used is 3-chloropropyltriethoxysilane, the antioxidant used is a mixture of 0.5 parts by weight of antioxidant 1010 and 0.3 parts by weight of antioxidant 168, the light stabilizer used is a mixture of 0.4 parts by weight of UV-326 and 0.4 parts by weight of HALS-770, and the reactive flame retardant plasticizer used is prepared by the following steps: S101. Under a nitrogen atmosphere, 18 parts by mass of 2-amino-5-nitrobenzoic acid, 7.2 parts by mass of acetone, 0.7 parts by mass of N,N-dimethylformamide, and 100 parts by mass of polyphosphoric acid were mixed and reacted at 120°C for 6 hours. After the reaction was completed, the reaction solution was poured into a saturated sodium bicarbonate solution, the precipitate was separated by filtration, and the precipitate was washed with deionized water until neutral and then purified by silica gel column chromatography to obtain 2-methyl-6-nitroquinoline-4-ol. S102. Under a nitrogen atmosphere, 26 parts by mass of n-octanol, 15 parts by mass of phosphorus oxychloride, 24 parts by mass of triethylamine and 260 parts by mass of dichloroethane are mixed and reacted at 20°C for 24 hours. After the reaction is completed, the triethylamine hydrochloride is removed by filtration, and then the solvent and excess triethylamine in the filtrate are removed by rotary evaporation to obtain the flame retardant precursor. S103. Under a nitrogen atmosphere, 12 parts by mass of 2-methyl-6-nitroquinoline-4-ol, 27 parts by mass of flame retardant precursor, 9.8 parts by mass of triethylamine, and 200 parts by mass of dichloroethane were mixed and reacted at 40°C for 24 hours. After the reaction was completed, the solvent in the reaction solution was removed by rotary evaporation. The remaining solid was then washed with deionized water and dried to obtain the flame retardant plasticizer precursor. S104. Under a nitrogen atmosphere, 24 parts by mass of flame retardant plasticizer precursor, 9.4 parts by mass of zinc powder, 11.6 parts by mass of ammonium chloride, 96 parts by mass of anhydrous ethanol, and 36 parts by mass of deionized water are mixed and reacted at 80°C for 4 hours. After the reaction is completed, the reaction solution is poured into a saturated sodium bicarbonate solution and then extracted with ethyl acetate. After separating the organic phase, the solvent is removed by rotary evaporation of the organic phase to obtain the flame retardant plasticizer. S105. Mix 3.8 parts by mass of acryloyl chloride, 18 parts by mass of flame retardant plasticizer, 4.7 parts by mass of triethylamine, and 100 parts by mass of dichloroethane and react at 0°C for 3 hours. After the reaction is completed, remove the solvent from the reaction solution by rotary evaporation, and wash the remaining solid with deionized water and dry it to obtain the reactive flame retardant plasticizer.

[0036] A method for preparing an extrusion-resistant and abrasion-resistant cable, comprising: S201. Mix 8 parts by mass of reinforcing filler, 1 part by mass of silane coupling agent, and 80 parts by mass of 40% (v / v) ethanol aqueous solution and react at 40°C for 6 hours. After the reaction is complete, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler.

[0037] S202. The thermoplastic polyurethane elastomer, reactive flame retardant plasticizer, and initiator are mixed and added to a screw extruder. The mixture is then melt-extruded and granulated at a temperature of 170°C to obtain a modified thermoplastic polyurethane elastomer. S203. The conductor core 1, which is stranded into conductors, is arranged in parallel. An insulating silicone rubber layer 2 is wrapped around the conductor, and a polypropylene filler rope 3 is used to fill the gap. A tinned copper wire shielding layer 4 is woven to wrap the conductor core 1 and the polypropylene filler rope 3 together. Then, a galvanized steel wire armor layer 5 is woven around the tinned copper wire shielding layer 4. S204. Polyvinyl chloride, modified thermoplastic polyurethane elastomer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant, and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 165℃, the mixture is coated onto the outside of the galvanized steel wire armor layer 5 to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 80℃ for 8 hours to form an outer sheath 6 on the outside of the galvanized steel wire armor layer 5, thus obtaining an extrusion-resistant and wear-resistant cable. Example

[0038] like Figure 1 The extrusion-resistant and wear-resistant cable includes, from the inside out, a conductor core 1, an insulating silicone rubber layer 2, a polypropylene filler rope 3, a tinned copper wire shielding layer 4, a galvanized steel wire armor layer 5, and an outer sheath 6.

[0039] In this embodiment, the outer protective layer comprises the following parts by weight of raw materials: 100 parts by weight of polyvinyl chloride, 30 parts by weight of thermoplastic polyurethane elastomer, 7.5 parts by weight of reactive flame retardant plasticizer, 6.5 parts by weight of secondary flame retardant, 0.3 parts by weight of initiator, 4 parts by weight of heat stabilizer, 22.5 parts by weight of plasticizer, 12 parts by weight of reinforcing filler, 1.5 parts by weight of silane coupling agent, 1.5 parts by weight of lubricant, 1.2 parts by weight of antioxidant, and 1.2 parts by weight of light stabilizer.

[0040] In this embodiment, the thermoplastic polyurethane elastomer used is a polyester-type thermoplastic polyurethane elastomer with a Shore A hardness of 82. The secondary flame retardant used is antimony trioxide, the initiator used is dicumyl peroxide, the heat stabilizer used is calcium-zinc stabilizer CZ108, the plasticizer used is a mixture of 2.5 parts by weight of epoxidized soybean oil and 20 parts by weight of diisononyl cyclohexane-1,2-dicarboxylate, the reinforcing filler used is calcined kaolin, the lubricant used is oxidized polyethylene wax, the silane coupling agent used is a mixture of 1 part by weight of 3-chloropropyltrimethoxysilane and 0.5 parts by weight of 3-bromopropyltrimethoxysilane, the antioxidant used is a mixture of 0.9 parts by weight of 1035 and 0.3 parts by weight of antioxidant 168, the light stabilizer used is a mixture of 0.6 parts by weight of UV-327 and 0.6 parts by weight of HALS-622, and the reactive flame retardant plasticizer used is prepared by the following steps: S101. Under a nitrogen atmosphere, 18 parts by mass of 2-amino-5-nitrobenzoic acid, 9 parts by mass of acetone, 1 part by mass of N,N-dimethylformamide, and 125 parts by mass of polyphosphoric acid were mixed and reacted at 130°C for 5 hours. After the reaction was completed, the reaction solution was poured into a saturated sodium bicarbonate solution, the precipitate was separated by filtration, and the precipitate was washed with deionized water until neutral and then purified by silica gel column chromatography to obtain 2-methyl-6-nitroquinoline-4-ol. S102. Under a nitrogen atmosphere, 31.5 parts by mass of n-decyl alcohol, 15 parts by mass of phosphorus oxychloride, 27 parts by mass of triethylamine and 290 parts by mass of dichloroethane are mixed and reacted at 40°C for 12 hours. After the reaction is completed, triethylamine hydrochloride is removed by filtration, and then the solvent and excess triethylamine in the filtrate are removed by rotary evaporation to obtain the flame retardant precursor. S103. Under a nitrogen atmosphere, 12 parts by mass of 2-methyl-6-nitroquinoline-4-ol, 31 parts by mass of flame retardant precursor, 11 parts by mass of triethylamine, and 220 parts by mass of dichloroethane were mixed and reacted at 50°C for 18 hours. After the reaction was completed, the solvent in the reaction solution was removed by rotary evaporation. The remaining solid was then washed with deionized water and dried to obtain the flame retardant plasticizer precursor. S104. Under a nitrogen atmosphere, 27 parts by mass of flame retardant plasticizer precursor, 12.5 parts by mass of zinc powder, 13.5 parts by mass of ammonium chloride, 108 parts by mass of anhydrous ethanol, and 42 parts by mass of deionized water are mixed and reacted at 85°C for 3 hours. After the reaction is completed, the reaction solution is poured into a saturated sodium bicarbonate solution and then extracted with ethyl acetate. After separating the organic phase, the solvent is removed by rotary evaporation of the organic phase to obtain the flame retardant plasticizer. S105. Mix 4.5 parts by mass of acryloyl chloride, 20 parts by mass of flame retardant plasticizer, 5.3 parts by mass of triethylamine, and 110 parts by mass of dichloroethane and react at 10°C for 2 hours. After the reaction is completed, remove the solvent from the reaction solution by rotary evaporation, and wash the remaining solid with deionized water and dry it to obtain the reactive flame retardant plasticizer.

[0041] A method for preparing an extrusion-resistant and abrasion-resistant cable, comprising: S201. Mix 12 parts by mass of reinforcing filler, 1.5 parts by mass of silane coupling agent, and 120 parts by mass of 50% ethanol aqueous solution and react at 50°C for 4.5 h. After the reaction is complete, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler.

[0042] S202. The thermoplastic polyurethane elastomer, reactive flame retardant plasticizer, and initiator are mixed and added to a screw extruder. The mixture is then melt-extruded and granulated at a temperature of 175°C to obtain a modified thermoplastic polyurethane elastomer. S203. The conductor core 1, which is stranded into conductors, is arranged in parallel. An insulating silicone rubber layer 2 is wrapped around the conductor, and a polypropylene filler rope 3 is used to fill the gap. A tinned copper wire shielding layer 4 is woven to wrap the conductor core 1 and the polypropylene filler rope 3 together. Then, a galvanized steel wire armor layer 5 is woven around the tinned copper wire shielding layer 4. S204. Polyvinyl chloride, modified thermoplastic polyurethane elastomer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant, and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 170°C, the mixture is coated onto the outside of the galvanized steel wire armor layer 5 to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 90°C for 6 hours to form an outer sheath 6 on the outside of the galvanized steel wire armor layer 5, thus obtaining an extrusion-resistant and wear-resistant cable. Example

[0043] like Figure 1 The extrusion-resistant and wear-resistant cable includes, from the inside out, a conductor core 1, an insulating silicone rubber layer 2, a polypropylene filler rope 3, a tinned copper wire shielding layer 4, a galvanized steel wire armor layer 5, and an outer sheath 6.

[0044] In this embodiment, the outer protective layer comprises the following parts by weight of raw materials: 100 parts by weight of polyvinyl chloride, 40 parts by weight of thermoplastic polyurethane elastomer, 10 parts by weight of reactive flame retardant plasticizer, 8 parts by weight of secondary flame retardant, 0.5 parts by weight of initiator, 5 parts by weight of heat stabilizer, 30 parts by weight of plasticizer, 15 parts by weight of reinforcing filler, 2.5 parts by weight of silane coupling agent, 2 parts by weight of lubricant, 1.5 parts by weight of antioxidant, and 1.5 parts by weight of light stabilizer.

[0045] In this embodiment, the thermoplastic polyurethane elastomer used is a polyester-type thermoplastic polyurethane elastomer with a Shore A hardness of 82. The secondary flame retardant used is zinc borate, the initiator used is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, the heat stabilizer used is calcium-zinc stabilizer CZ113, the plasticizer used is a mixture of 5 parts by weight of epoxidized soybean oil and 25 parts by weight of trioctyl trimellitate, the reinforcing filler used is nano-silica, the lubricant used is oxidized polyethylene wax, the silane coupling agent used is 3-bromopropyltriethoxysilane, the antioxidant used is a mixture of 1 part by weight of antioxidant 1010 and 0.5 parts by weight of antioxidant 626, the light stabilizer used is a mixture of 0.5 parts by weight of UV-328 and 1 part by weight of HALS-770, and the reactive flame retardant plasticizer used is prepared by the following steps: S101. Under a nitrogen atmosphere, 18 parts by mass of 2-amino-5-nitrobenzoic acid, 10.8 parts by mass of acetone, 1.4 parts by mass of N,N-dimethylformamide, and 150 parts by mass of polyphosphoric acid were mixed and reacted at 140℃ for 4 hours. After the reaction was completed, the reaction solution was poured into a saturated sodium bicarbonate solution, the precipitate was separated by filtration, and the precipitate was washed with deionized water until neutral and then purified by silica gel column chromatography to obtain 2-methyl-6-nitroquinoline-4-ol. S102. Under a nitrogen atmosphere, 37 parts by mass of lauryl alcohol, 15 parts by mass of phosphorus oxychloride, 30 parts by mass of triethylamine and 320 parts by mass of dichloroethane are mixed and reacted at 60°C for 6 hours. After the reaction is completed, the triethylamine hydrochloride is removed by filtration, and then the solvent and excess triethylamine in the filtrate are removed by rotary evaporation to obtain the flame retardant precursor. S103. Under a nitrogen atmosphere, 12 parts by mass of 2-methyl-6-nitroquinoline-4-ol, 35 parts by mass of flame retardant precursor, 12.2 parts by mass of triethylamine, and 240 parts by mass of dichloroethane were mixed and reacted at 60°C for 12 hours. After the reaction was completed, the solvent in the reaction solution was removed by rotary evaporation. The remaining solid was then washed with deionized water and dried to obtain the flame retardant plasticizer precursor. S104. Under a nitrogen atmosphere, 30 parts by mass of flame retardant plasticizer precursor, 15.6 parts by mass of zinc powder, 15.4 parts by mass of ammonium chloride, 120 parts by mass of anhydrous ethanol, and 48 parts by mass of deionized water are mixed and reacted at 90°C for 2 hours. After the reaction is completed, the reaction solution is poured into a saturated sodium bicarbonate solution and then extracted with ethyl acetate. After separating the organic phase, the solvent is removed by rotary evaporation of the organic phase to obtain the flame retardant plasticizer. S105. Mix 5.2 parts by mass of acryloyl chloride, 22 parts by mass of flame retardant plasticizer, 5.9 parts by mass of triethylamine, and 120 parts by mass of dichloroethane and react at 20°C for 1 hour. After the reaction is completed, remove the solvent from the reaction solution by rotary evaporation, and wash the remaining solid with deionized water and dry it to obtain the reactive flame retardant plasticizer.

[0046] A method for preparing an extrusion-resistant and abrasion-resistant cable, comprising: S201. Mix 15 parts by mass of reinforcing filler, 2.5 parts by mass of silane coupling agent, and 150 parts by mass of 60% ethanol aqueous solution and react at 60°C for 3 hours. After the reaction is completed, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler.

[0047] S202. The thermoplastic polyurethane elastomer, reactive flame retardant plasticizer, and initiator are mixed and added to a screw extruder. The mixture is then melt-extruded and granulated at a temperature of 180°C to obtain the modified thermoplastic polyurethane elastomer. S203. The conductor core 1, which is stranded into conductors, is arranged in parallel. An insulating silicone rubber layer 2 is wrapped around the conductor, and a polypropylene filler rope 3 is used to fill the gap. A tinned copper wire shielding layer 4 is woven to wrap the conductor core 1 and the polypropylene filler rope 3 together. Then, a galvanized steel wire armor layer 5 is woven around the tinned copper wire shielding layer 4. S204. Polyvinyl chloride, modified thermoplastic polyurethane elastomer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant, and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 175°C, the mixture is coated onto the outside of the galvanized steel wire armor layer 5 to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 100°C for 4 hours to form an outer sheath 6 on the outside of the galvanized steel wire armor layer 5, thus obtaining an extrusion-resistant and wear-resistant cable.

[0048] Comparative Example 1 The difference between this comparative example and Example 3 is that no reactive flame retardant plasticizer was prepared, nor was the thermoplastic polyurethane elastomer grafted or modified.

[0049] An extrusion-resistant and abrasion-resistant cable includes, from the inside out, a conductor core, an insulating silicone rubber layer, a polypropylene filler rope, a tinned copper wire shielding layer, a galvanized steel wire armor layer, and an outer sheath.

[0050] In this comparison, the outer sheath contains the following parts by weight of raw materials: 100 parts by weight of polyvinyl chloride, 40 parts by weight of thermoplastic polyurethane elastomer, 8 parts by weight of secondary flame retardant, 5 parts by weight of heat stabilizer, 30 parts by weight of plasticizer, 15 parts by weight of reinforcing filler, 2.5 parts by weight of silane coupling agent, 2 parts by weight of lubricant, 1.5 parts by weight of antioxidant, and 1.5 parts by weight of light stabilizer.

[0051] In this embodiment, the thermoplastic polyurethane elastomer used is a polyester-type thermoplastic polyurethane elastomer with a Shore A hardness of 82. The secondary flame retardant used is zinc borate, the heat stabilizer used is calcium-zinc stabilizer CZ113, the plasticizer used is a mixture of 5 parts by mass of epoxidized soybean oil and 25 parts by mass of trioctyl trimellitate, the reinforcing filler used is nano-silica, the lubricant used is oxidized polyethylene wax, the silane coupling agent used is 3-bromopropyltriethoxysilane, the antioxidant used is a mixture of 1 part by mass of antioxidant 1010 and 0.5 parts by mass of antioxidant 626, and the light stabilizer used is a mixture of 0.5 parts by mass of UV-328 and 1 part by mass of HALS-770.

[0052] A method for preparing an extrusion-resistant and abrasion-resistant cable, comprising: S201. Mix 15 parts by mass of reinforcing filler, 2.5 parts by mass of silane coupling agent, and 150 parts by mass of 60% ethanol aqueous solution and react at 60°C for 3 hours. After the reaction is completed, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler.

[0053] S202. The conductor cores of the conductor stranded together are arranged in parallel. An insulating silicone rubber layer is wrapped around the conductor, and the gaps are filled with polypropylene filler rope. A tinned copper wire shielding layer is woven to wrap the conductor cores and polypropylene filler rope together. Then, a galvanized steel wire armoring layer is woven outside the tinned copper wire shielding layer. S203. Polyvinyl chloride, thermoplastic polyurethane elastomer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant, and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 175℃, the mixture is coated onto the outside of a galvanized steel wire armor layer to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 100℃ for 4 hours to form an outer sheath layer on the outside of the galvanized steel wire armor layer, thus obtaining an extrusion-resistant and wear-resistant cable.

[0054] Comparative Example 2 The difference between this comparative example and Example 3 is that the thermoplastic polyurethane elastomer is not modified by grafting reactive flame retardant plasticizers onto it.

[0055] An extrusion-resistant and abrasion-resistant cable includes, from the inside out, a conductor core, an insulating silicone rubber layer, a polypropylene filler rope, a tinned copper wire shielding layer, a galvanized steel wire armor layer, and an outer sheath.

[0056] In this comparative example, the outer protective layer comprises the following parts by weight of raw materials: 100 parts by weight of polyvinyl chloride, 40 parts by weight of thermoplastic polyurethane elastomer, 10 parts by weight of reactive flame retardant plasticizer, 8 parts by weight of secondary flame retardant, 5 parts by weight of heat stabilizer, 30 parts by weight of plasticizer, 15 parts by weight of reinforcing filler, 2.5 parts by weight of silane coupling agent, 2 parts by weight of lubricant, 1.5 parts by weight of antioxidant, and 1.5 parts by weight of light stabilizer.

[0057] In this embodiment, the thermoplastic polyurethane elastomer used is a polyester-type thermoplastic polyurethane elastomer with a Shore A hardness of 82. The secondary flame retardant used is zinc borate, the heat stabilizer used is calcium-zinc stabilizer CZ113, the plasticizer used is a mixture of 5 parts by weight of epoxidized soybean oil and 25 parts by weight of trioctyl trimellitate, the reinforcing filler used is nano-silica, the lubricant used is oxidized polyethylene wax, the silane coupling agent used is 3-bromopropyltriethoxysilane, the antioxidant used is a mixture of 1 part by weight of antioxidant 1010 and 0.5 parts by weight of antioxidant 626, the light stabilizer used is a mixture of 0.5 parts by weight of UV-328 and 1 part by weight of HALS-770, and the reactive flame retardant plasticizer used is prepared by the following steps: S101. Under a nitrogen atmosphere, 18 parts by mass of 2-amino-5-nitrobenzoic acid, 10.8 parts by mass of acetone, 1.4 parts by mass of N,N-dimethylformamide, and 150 parts by mass of polyphosphoric acid were mixed and reacted at 140℃ for 4 hours. After the reaction was completed, the reaction solution was poured into a saturated sodium bicarbonate solution, the precipitate was separated by filtration, and the precipitate was washed with deionized water until neutral and then purified by silica gel column chromatography to obtain 2-methyl-6-nitroquinoline-4-ol. S102. Under a nitrogen atmosphere, 37 parts by mass of lauryl alcohol, 15 parts by mass of phosphorus oxychloride, 30 parts by mass of triethylamine and 320 parts by mass of dichloroethane are mixed and reacted at 60°C for 6 hours. After the reaction is completed, the triethylamine hydrochloride is removed by filtration, and then the solvent and excess triethylamine in the filtrate are removed by rotary evaporation to obtain the flame retardant precursor. S103. Under a nitrogen atmosphere, 12 parts by mass of 2-methyl-6-nitroquinoline-4-ol, 35 parts by mass of flame retardant precursor, 12.2 parts by mass of triethylamine, and 240 parts by mass of dichloroethane were mixed and reacted at 60°C for 12 hours. After the reaction was completed, the solvent in the reaction solution was removed by rotary evaporation. The remaining solid was then washed with deionized water and dried to obtain the flame retardant plasticizer precursor. S104. Under a nitrogen atmosphere, 30 parts by mass of flame retardant plasticizer precursor, 15.6 parts by mass of zinc powder, 15.4 parts by mass of ammonium chloride, 120 parts by mass of anhydrous ethanol, and 48 parts by mass of deionized water are mixed and reacted at 90°C for 2 hours. After the reaction is completed, the reaction solution is poured into a saturated sodium bicarbonate solution and then extracted with ethyl acetate. After separating the organic phase, the solvent is removed by rotary evaporation of the organic phase to obtain the flame retardant plasticizer. S105. Mix 5.2 parts by mass of acryloyl chloride, 22 parts by mass of flame retardant plasticizer, 5.9 parts by mass of triethylamine, and 120 parts by mass of dichloroethane and react at 20°C for 1 hour. After the reaction is completed, remove the solvent from the reaction solution by rotary evaporation, and wash the remaining solid with deionized water and dry it to obtain the reactive flame retardant plasticizer.

[0058] A method for preparing an extrusion-resistant and abrasion-resistant cable, comprising: S201. Mix 15 parts by mass of reinforcing filler, 2.5 parts by mass of silane coupling agent, and 150 parts by mass of 60% ethanol aqueous solution and react at 60°C for 3 hours. After the reaction is completed, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler.

[0059] S202. The conductor cores of the conductor stranded together are arranged in parallel. An insulating silicone rubber layer is wrapped around the conductor, and the gaps are filled with polypropylene filler rope. A tinned copper wire shielding layer is woven to wrap the conductor cores and polypropylene filler rope together. Then, a galvanized steel wire armoring layer is woven outside the tinned copper wire shielding layer. S203. Polyvinyl chloride, thermoplastic polyurethane elastomer, reactive flame retardant plasticizer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant, and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 175°C, the mixture is coated onto the outside of a galvanized steel wire armor layer to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 100°C for 4 hours to form an outer sheath layer on the outside of the galvanized steel wire armor layer, thus obtaining an extrusion-resistant and wear-resistant cable.

[0060] Experimental Example 1 The reactive flame retardant plasticizer obtained in Example 1 was mixed and ground with potassium bromide powder and then pressed into transparent sheets. The infrared spectrum was obtained by scanning in the wavenumber range of 500 to 4000 cm using a Nexus 670 Fourier transform infrared spectroscopy system (Thermo Nicolet, USA) equipped with a DTGS detector.

[0061] like Figure 3 As shown, at 3275cm -1 An absorption peak for the stretching vibration of amide NH was observed at 3044 cm⁻¹. -1 An absorption peak for the CH stretching vibration on the quinoline ring was observed at 2963 cm⁻¹. -1 An absorption peak for the stretching vibration of long-chain alkyl groups was observed at 1666 cm⁻¹. -1 An absorption peak for the C=O stretching vibration of the amide structure was observed at 1634 cm⁻¹. -1 An absorption peak for the stretching vibration of the terminal double bond was observed at 1610 cm⁻¹. -1 Location, 1583cm-1 Location, 1563cm -1 Multiple absorption peaks of C=C and C=N stretching vibrations on the quinoline ring were observed at 1468 cm⁻¹. -1 Shear vibration absorption peaks of long-chain alkyl groups were observed at 1262 cm⁻¹. -1 An absorption peak for the CN stretching vibration of the quinoline ring was observed at 1230 cm⁻¹. -1 An absorption peak for the P=O stretching vibration of the phosphate ester structure was observed at 965 cm⁻¹. -1 The absorption peaks of the POC stretching vibration of the phosphate ester structure were observed. These absorption peaks confirm that the desired reactive flame retardant plasticizer was successfully prepared by this invention.

[0062] Experimental Example 2 The outer sheath of the cable samples obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests, and the test results are shown in Table 1.

[0063] Tensile property test: The tensile strength and elongation at break of the specimens were tested in accordance with the national standard GB / T 1040.3-2006.

[0064] Shape stability: The compression set (70℃×24h, 25% compression) and elastic recovery rate of the specimens were tested in accordance with the national standard GB / T 7759.1-2015.

[0065] Wear resistance test: The wear amount of the test specimen was tested according to the national standard GB / T 9867-2008 (wear stroke is 40m).

[0066] Plasticizer migration test: The amount of plasticizer migration in the test sample was tested according to the national standard GB / T 1690-2010 (70℃×24h, n-hexane).

[0067] Flame retardant performance test: The oxygen limiting index of the test specimen was tested in accordance with the national standard GB / T 2406.2-2009.

[0068] Table 1

[0069] As can be seen from Table 1, the outer sheath samples of the present invention in Examples 1-3 have better mechanical properties, elasticity, and wear resistance. Using the samples of the present invention as the outer sheath of the cable enables the cable to have both good extrusion resistance and wear resistance. In Comparative Example 2, the reactive flame retardant plasticizer was not grafted onto the thermoplastic polyurethane elastomer, which has poor compatibility with the reactive flame retardant plasticizer. The reactive flame retardant plasticizer tends to accumulate only in the polyvinyl chloride phase and cannot play a compatibilizing role. As a result, the comprehensive performance of the samples in Comparative Example 2 decreased to varying degrees. Furthermore, since the dispersion uniformity of the ungrafted reactive flame retardant plasticizer in the matrix is ​​far inferior to that of the grafted sample in Example 3, even if the amount of flame retardant component added is the same, the oxygen limiting index of the sample in Comparative Example 2 is still lower than that of the sample in Example 3.

[0070] The above description is merely a preferred embodiment of this application, but the scope of protection of this application is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in this application, based on the technical solution and inventive concept of this application, should be included within the scope of protection of this application.

Claims

1. A compression-resistant and abrasion-resistant cable, characterized in that, It contains the following raw materials: conductor core (1), insulating silicone rubber layer (2), polypropylene filler rope (3), tinned copper wire shielding layer (4), galvanized steel wire armor layer (5), and outer sheath (6), arranged sequentially from the inside out. The outer protective layer comprises the following raw materials in parts by weight: 100 parts by weight of polyvinyl chloride, 20-40 parts by weight of thermoplastic polyurethane elastomer, 5-10 parts by weight of reactive flame retardant plasticizer, 5-8 parts by weight of secondary flame retardant, 0.1-0.5 parts by weight of initiator, 3-5 parts by weight of heat stabilizer, 15-30 parts by weight of plasticizer, 8-15 parts by weight of reinforcing filler, 1-2.5 parts by weight of silane coupling agent, 0.5-2 parts by weight of lubricant, 0.8-1.5 parts by weight of antioxidant, and 0.8-1.5 parts by weight of light stabilizer; The reactive flame retardant plasticizer is prepared by the following steps: 2-Amino-5-nitrobenzoic acid is reacted with acetone to obtain 2-methyl-6-nitroquinoline-4-ol; long-chain fatty alcohol is reacted with phosphorus oxychloride to obtain a flame retardant precursor; 2-methyl-6-nitroquinoline-4-ol is reacted with the flame retardant precursor to obtain a flame retardant plasticizer precursor; the flame retardant plasticizer precursor is reduced with zinc powder to obtain a flame retardant plasticizer; and the flame retardant plasticizer is reacted with acryloyl chloride to obtain a reactive flame retardant plasticizer. The long-chain fatty alcohol is at least one of n-octanol, n-decanol, and lauryl alcohol.

2. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The reactive flame-retardant plasticizer is prepared by the following steps: S101. Under a nitrogen atmosphere, 18 parts by mass of 2-amino-5-nitrobenzoic acid, 7.2-10.8 parts by mass of acetone, 0.7-1.4 parts by mass of N,N-dimethylformamide, and 100-150 parts by mass of polyphosphoric acid are mixed and reacted at a temperature of 120-140°C to obtain 2-methyl-6-nitroquinoline-4-ol; S102. Under a nitrogen atmosphere, 26-37 parts by mass of long-chain fatty alcohol, 15 parts by mass of phosphorus oxychloride, 24-30 parts by mass of triethylamine, and 260-320 parts by mass of dichloroethane are mixed and reacted at a temperature of 20-60°C to obtain a flame retardant precursor. S103. Under a nitrogen atmosphere, 12 parts by mass of 2-methyl-6-nitroquinoline-4-ol, 27-35 parts by mass of flame retardant precursor, 9.8-12.2 parts by mass of triethylamine, and 200-240 parts by mass of dichloroethane are mixed and reacted at a temperature of 40-60°C to obtain a flame retardant plasticizer precursor. S104. Under a nitrogen atmosphere, 24-30 parts by weight of flame retardant plasticizer precursor, 9.4-15.6 parts by weight of zinc powder, 11.6-15.4 parts by weight of ammonium chloride, 96-120 parts by weight of anhydrous ethanol, and 36-48 parts by weight of deionized water are mixed and reacted at a temperature of 80-90°C to obtain a flame retardant plasticizer. S105: Mix 3.8–5.2 parts by weight of acryloyl chloride, 18–22 parts by weight of flame retardant plasticizer, 4.7–5.9 parts by weight of triethylamine, and 100–120 parts by weight of dichloroethane and react them at a temperature of 0–20°C to obtain a reactive flame retardant plasticizer.

3. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The secondary flame retardant is at least one of antimony trioxide and zinc borate.

4. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The initiator is at least one of dicumyl peroxide and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

5. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The heat stabilizer is at least one of calcium-zinc stabilizer CZ108 and calcium-zinc stabilizer CZ113.

6. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The plasticizer is at least one of epoxidized soybean oil, trioctyl trimellitate, and diisononyl cyclohexane-1,2-dicarboxylate.

7. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The reinforcing filler is at least one of nano-calcium carbonate, nano-silica, and calcined kaolin.

8. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The lubricant is at least one of polyethylene wax and oxidized polyethylene wax.

9. The extrusion-resistant and abrasion-resistant cable according to claim 1, characterized in that, The silane coupling agent is at least one of 3-chloropropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-bromopropyltriethoxysilane, and 3-bromopropyltrimethoxysilane; the antioxidant is at least one of antioxidant 1010, antioxidant 1035, antioxidant 168, and antioxidant 626; and the light stabilizer is at least one of UV-326, UV-327, UV-328, HALS-770, and HALS-622.

10. A method for preparing an extrusion-resistant and abrasion-resistant cable as described in any one of claims 1 to 9, characterized in that, Includes the following steps: S201. Mix 8-15 parts by mass of reinforcing filler, 1-2.5 parts by mass of silane coupling agent, and 80-150 parts by mass of 40-60% ethanol aqueous solution and react at 40-60℃ for 3-6 hours. After the reaction is completed, filter out the solid and wash the obtained solid with deionized water and dry it to obtain the modified reinforcing filler. S202. The thermoplastic polyurethane elastomer, reactive flame retardant plasticizer, and initiator are mixed and added to a screw extruder. The mixture is then melt-extruded and granulated at a temperature of 170-180℃ to obtain the modified thermoplastic polyurethane elastomer. S203. The conductor core (1) formed by stranding the conductors is arranged in parallel. An insulating silicone rubber layer (2) is wrapped around the conductor. The gap is filled with polypropylene filler rope (3). A tinned copper wire shielding layer (4) is woven to wrap the conductor core (1) and the polypropylene filler rope (3) together. Then, a galvanized steel wire armor layer (5) is woven around the tinned copper wire shielding layer (4). S204. Polyvinyl chloride, modified thermoplastic polyurethane elastomer, modified reinforcing filler, secondary flame retardant, heat stabilizer, plasticizer, lubricant, antioxidant and light stabilizer are mixed and added to a screw extruder. After melt extrusion at a temperature of 165-175℃, the mixture is coated on the outside of the galvanized steel wire armor layer (5) to obtain a rough extrusion-resistant and wear-resistant cable. Then, the rough extrusion-resistant and wear-resistant cable is placed in an oven at a temperature of 80-100℃ for 4-8 hours to form an outer sheath (6) on the outside of the galvanized steel wire armor layer (5) to obtain an extrusion-resistant and wear-resistant cable.